2021
DOI: 10.3289/geomar_rep_ns_57_20
|View full text |Cite
|
Sign up to set email alerts
|

RV SONNE Fahrtbericht / Cruise Report SO277 OMAX: Offshore Malta Aquifer Exploration, Emden (Germany) – Emden (Germany), 14.08. – 03.10.2020

Abstract: SO277 OMAX served two scientific projects. The objectives of the first project, SMART, were to develop multi-disciplinary methodologies to detect, quantify, and model offshore groundwater reservoirs in regions dominated by carbonate geology such as the Mediterranean Sea. To this end we acquired controlled-source electromagnetic, seismic, hydroacoustic, geochemical, seafloor imagery data off Malta. Preliminary evaluation of the geophysical data show that there are resisitivity anomalies that may represent offsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…The observed resistivities are 2–5 times larger than the background seawater‐saturated UCL resistivities along lines 5 and 6. Both R1 and R3 extend to the seafloor, yet no freshened groundwater discharge was registered by the CTD (conductivity, temperature, depth) sensor (mounted on the CSEM system) and pore water sampling from gravity cores (Berndt et al., 2021). These observations, together with a lack of a confining unit above the resistivity anomalies, suggest that the latter are unlikely to be associated with OFG.…”
Section: Discussionmentioning
confidence: 99%
“…The observed resistivities are 2–5 times larger than the background seawater‐saturated UCL resistivities along lines 5 and 6. Both R1 and R3 extend to the seafloor, yet no freshened groundwater discharge was registered by the CTD (conductivity, temperature, depth) sensor (mounted on the CSEM system) and pore water sampling from gravity cores (Berndt et al., 2021). These observations, together with a lack of a confining unit above the resistivity anomalies, suggest that the latter are unlikely to be associated with OFG.…”
Section: Discussionmentioning
confidence: 99%
“…Closer to the seafloor, the lack of subhorizontal HRS (Figure 4c) suggests that gas migration is mostly subvertical even though seafloor seepage does occur (Berndt, 2013). A highly reflective patch of the seafloor west of the active seep site contains massive carbonates based on video observations (Berndt, 2013), but no gas flares have been found in hydroacoustic data. The fluid flow system underneath these carbonates might be intermittent because gas hydrate may periodically clog the vertical flow pathways feeding the seafloor vent.…”
Section: Discussionmentioning
confidence: 99%
“…At a large scale, BSRs cover an area of more than 15,000 km 2 both in the accretionary wedge and in the SCS (Chi et al, 1998; Liu et al, 2006). In addition, Lin et al (2009) investigated geological controls on gas hydrate occurrences in the area SW of Taiwan, while hydroacoustic data and geochemical data sets derived from sediment cores and bottom‐water samples (Berndt, 2013; Chen et al, 2017; Chiu et al, 2006; Chuang et al, 2010; Liu et al, 2006; Oung et al, 2006) identified hydrate related fluid venting in the region. Also, seafloor photographs by deep‐tow camera systems and sediment samplers show carbonates, carbonate mounds, chimney structures, and chemosynthetic communities associated with bacterial mats (Berndt, 2013).…”
Section: Geologic Settingmentioning
confidence: 99%
“…One multichannel seismic reflection profile (P2000_2115_2857), obtained by RV Sonne expedition SO277 (Berndt et al, 2021), was taken into consideration. The profile crosses the shelf across the study area (Figure 2A, right transect).…”
Section: Seismic Reflection Profilementioning
confidence: 99%